SEMANGAT PELAYANAN YESUS KEPADA ORANG MISKIN MENURUT INJIL LUKAS 9:10-17 DAN RELEVANSINYA BAGI KARYA PELAYANAN KATEKIS DEWASA INI - Ola Rongan Wilhelmus; Margareta Sudaryanti (Bahasa Indonesia, 2018)
The poor in Luke 9:10-17 refers to those who lack of food, suffering various physical illness and those who are yearning for God. The main reason for Jesus to deliver such services for the poor is because Jesus is a good shepherd who has to present the love of God to God's peoples. The most concrete of Jesus' services to the poor revealed by the power of Himself to feed the hungers, to heal the illness, and to spread the Kingdom (love) of God to those who are yearning for God's love and help. After doing glorious things for the poor, Jesus then demanding those who have been experiencing God's love to be more faithful to God and doing good things for others. The research applied a qualitative method which tried to collect and analyze data of the study verbally. This means that the research did not apply a statistical method in analyzing data. The reason of choosing qualitative method is due to the data of study collected directly in the field of study through a so-called in-depth interview with respondents of the study. Aside from this, qualitative research could be cultivated to construct a more comprehensive information and knowledge pertaining to the subject being studied. The results of data analysis shown that majority of respondents basicallyhad shown particular concerns to the poor. Concrete concerns were revealed by respondents in empowering the poor throughout SSV's programs related toagricultural activities, animal husbandry and scholarship aid. The challenges experienced by respondents in helping the poor were related to the limitation of their times, energies, and financial resources. Even though, the respondents said that they have had tried their best to overcome those challenges by spending a more regular times to involve with the poor, spending some of their monthly incomes for the poor; strengthening their own faith on God, encouraging others to help the poor, and to educate and guide the poor to be self-help.